Educational Transformation Process through the Role of Leader Teachers at SMP Negeri 1 Tolitoli - Nursida; Waris Tasrim, Isnada (Journal of Educational Management and Islamic Leadership (JEMIL), 2024)
Educational Transformation Process through the Role of Leader Teachers at SMP Negeri 1 Tolitoli Penelitian tentang proses transformasi pendidikan melalui peran guru penggerak dilakukan dengan tujuan 1) untuk menganalisis proses transformasi pembelajaran di SMP Negeri 1 Tolitoli melalui peran guru penggerak , 2) untuk menganalisis proses transformasi ekosistem di SMP Negeri 1 Tolitoli melalui peran guru penggerak. Penelitian ini menggunakan metode penelitian kualitatif. Prosedur pengumpulan data dilakukan dengan wawancara, observasi dan studi dokumentasi. Teknik analisis data dengan alur pengumpulan data, reduksi data dan penyajian data. Keabsahan data menggunakan teknik triangulasi sumber dan triangulasi metode. Hasil penelitian menunjukkan: 1) Proses transformasi pembelajaran melalui peran guru penggerak meliputi a) metode pembelajaran sebagai inisiator dan pendorong bagi rekan guru, serta motivator bagi siswa; b) penggunaan teknologi sangat membantu guru dan siswa dalam pembelajaran;, c) pemberdayaan peserta didik dalam pembelajaran membawa perubahan yang signifikan terhadap siswa; 2) Proses transformasi ekosistem sekolah melalui peran guru penggerak meliputi : a) Peran guru penggerak sebagai inisiator dan pendorong dalam pengunaan teknologi pendidikan; b) Peran guru penggerak sebagai pendorong terciptanya budaya kolaborasi dan berbagi praktik baik. Research on the education transformation process through the role of leader teachers were conducted with the following objectives: 1) to analyze the learning transformation process in SMP Negeri 1 Tolitoli through the role of leader teachers, and 2) to analyze the ecosystem transformation process in SMP Negeri 1 Tolitoli through the role of leader teachers. This research employed a qualitative research method. Data collection procedures involved interviews, observations, and document studies. The data analysis technique followed a process of data collection, data reduction, and data presentation. Data validity was ensured through source triangulation and method triangulation. The results of the research are as follows: 1) the learning transformation process through the role of leader teachers includes a) teaching methods as initiators and motivators for fellow teachers, as well as motivators for students. b) The use of technology greatly aids teachers and students in learning. c) Empowering students in learning brings significant changes to students. 2) The school ecosystem transformation process through the role of leader teachers includes: a) the role of leader teachers as initiators and promoters of educational technology utilization. b) The role of leader teachers as promoters of collaborative culture and sharing best practices.